DNA barcoding of invasive Gambusia holbrooki Girard, 1859 and Atherina boyeri Risso, 1810 inhabiting Upper Euphrates River Basin, Türkiye - Eroglu, Mucahit; Celik, Isilay; Dusukcan, Mustafa; Unal, Esra Mine; Coban, Mehmet Zulfu; Gunduz, Fatih; Keskin, Emre (Nature Portfolio, 2025)
The main contributor to T & uuml;rkiye's abundant freshwater fish biodiversity is its geographic location. This fauna consists of endemic, native, and non-native fish species. The introduction of Gambusia holbrooki Girard, 1859 to Lake Amik in the 1920s for the biological control of malaria was the first introduction of nonnative species to T & uuml;rkiye. Atherina boyeri Risso, 1810 and other nonnative fish species have recently been introduced to T & uuml;rkiye's freshwaters. In this research, the first records of invasive Gambusia holbrooki (Keban Dam Lake, in Elaz & imath;& gbreve; Province) and Atherina boyeri (Karakaya Dam Lake, in Elaz & imath;& gbreve; Province) are cited from the Upper Euphrates River Basin in the Eastern Anatolia Region of T & uuml;rkiye. In situ electrofishing equipment was used to gather the specimens. Fish muscle samples were used to extract genomic DNA, which was then used to barcode the mitochondrial cytochrome c oxidase subunit I (COI) gene to identify different species of fish. The identification of invasive fish species using DNA barcoding is an effective technique, as evidenced by the comparison of amplified COI sequences to the BLAST database.
Keywords: COI; Invasive fish; Atherinidae; Poeciliidae; Keban Dam Lake; Karakaya Dam Lake